Digital Literacy and Learning Outcomes: Analyzing the Impact of Blended Learning in Higher Education during the Post-Pandemic Era - Handayani, Tri; Mokay, Meggy Merlin; Sukmayadi, Dodi; A. Fitriani; Belangi, Siska Putri (PT Inovasi Pratama Internasional, 2025)
This study examined the relationship between digital literacy competencies and learning outcomes through the implementation of blended learning models in Indonesian higher education institutions during the post-pandemic period. Employing a qualitative research methodology, this investigation utilized semi-structured interviews were conducted with 25 university students and 15 faculty members across five Indonesian universities, complemented by a document analysis of institutional policies and learning management system data. Through thematic analysis, following Braun and Clarke's six-phase approach, four primary themes emerged: (1) Digital Competency Development, (2) Pedagogical Transformation, (3) Learning Engagement Adaptation, and (4) Institutional Infrastructure Challenges. The findings revealed that students with higher digital literacy levels demonstrated enhanced learning outcomes in blended environments, characterized by improved critical thinking skills, increased collaborative engagement, and greater autonomous learning capabilities. However, significant disparities exist in digital access and competency levels, creating educational inequities that require institutional interventions. The study concludes that successful blended learning implementation necessitates comprehensive digital literacy development programs, robust technological infrastructure, and adaptive pedagogical strategies that bridge the digital divide, while enhancing educational quality in post-pandemic higher education contexts